Dampak Budaya Akademik Kampus Terhadap Gaya Hidup Mahasiswa Perantau Tadris IPS UIN Jakarta - Alfarauq, Farkhan Abdurochim; Syaripulloh, Syaripulloh; Ishaq, Rusli (Sosio-Didaktika: Social Science Education Journal, 2023)
This study aims to find out and explain how the impact of campus academic culture on the lifestyles of overseas students in the Social Sciences Tadris Study Program at UIN Syarif Hidayatullah Jakarta. The method used is qualitative with the data analysis model of Miles and Hubberman on the basis of Peter L. Berger's social construction theory and Weber's Social Action. The results of this study are that campus academic culture becomes a habit and becomes values and norms that have gone through an institutional process and are present in a tangible form. Overseas students absorb the objective world and try to strengthen their existence as students depending on their association. The next step is that overseas students try to display it. Campus academic culture is only considered as a requirement during lectures by overseas students or wetrationalat. Campus academic culture is not an indicator of the lifestyle that is displayed, overseas students tend to display a lifestyle in accordance with their previous interests or those they just discovered while undergoing lectures. Campus academic culture has a more positive impact on improving the ability of individual overseas students such as adding insight and changing mindsets that affect their lives.Keywords: Academic Culture, Overseas Students, and Lifestyle.